Web-based data collection yielded an additional response bias - but had no direct effect on outcome scales - Mayr, Andreas; Gefeller, Olaf; Prokosch, Hans-Ulrich; Pirkl, Anna; Fröhlich, Antje; de Zwaan, Matina (Journal of Clinical Epidemiology, 2012)
Objective: To assess and to evaluate possible effects arising from Web-based data collection on the results of a study. Study Design and Setting: We analyzed participants of the German Weight Control Registry (GWCR) of whom 328 chose to use Web-based questionnaires and 139 preferred to participate via a traditional postal survey. Furthermore, we included data of 212 individuals sampled independently from the general population who fulfilled the study's inclusion criteria - giving us the chance to differentiate between response bias (concerning Web-based data collection) and general selection bias (concerning participation in the GWCR). Results: In addition to selection bias (GWCR participants are overall better educated, more likely to live in a partnership, more often female, and older than the general population), we also found a substantial response bias: Participants using the Internet were younger, better educated, and more often male compared with participants preferring the paper-and-pencil version. However, after adjusting for these differences, we found no additional direct effect of Web-based data collection on any of the outcome variables. Conclusion: Web-based epidemiologic studies still do not attract the same participants as postal surveys, even in highly industrialized countries. However, after adjusting for this bias, the same results can be expected. © 2012 Elsevier Inc. All rights reserved.
UnivIS-Import:2015-04-14:Pub.2012.tech.IMMD.infome.webbas
Keywords: Bias; Data collection; Epidemiologic methods; Internet; Questionnaires; Registries